PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi pada Pelanggan Kartu SIM Tri di Purworejo) pada tahun 1991 dengan format Global System of Mobile Communications (GSM) - Adam Wicaksono (Prospect : Jurnal Manajemen dan Akuntansi, 2024)
The purpose of this research is to determine the effect of product quality and service quality on Tri SIM card customer satisfaction in Purworejo.The population is Tri SIM card customers in Purworejo with unknown data. Samples were taken using a purposive sampling technique of 100 respondents. The data analysis techniques used were validity testing, reliability testing, correlation coefficient, multiple linear regression analysis, coefficient of determination, t test and F test.The validity test results show that all statement items have a Pearson correlation value above the critical value limit, namely 0.3. The reliability test results show that the Cronbach's alpha value is more than0.70. The results of the correlation coefficient test show that the Pearson correlation value for product quality is 0.422, and service quality is 0.537. The results of the multiple linear regression test show a constant of 0.384, a b1 value of 0.309 and b2 of 0.541. The coefficient of determination test results show an Adjusted R square value of 0.312. The results of the t test show that the calculated t value for product quality is 2.345 (> 1.661) with a sig value of 0.021 (< 0.05), and the calculated t value for service quality is 4.625 (> 1.661) with a sig value of 0.003 (< 0.05). The F test results show an F value > 4, and a sig value of 0.000 (< 0.05).